Risk of Mortality for Proximal Femoral Fracture in Patients With and Without COVID-19. A Retrospective Cohort Study. (5th November 2022) - Holub, Ashley; Jornet-Gibert, Montsant; Ruppenkamp, Jill; Holy, Chantal E.; Daccach, Juan; Torner, Pere; Caba-Doussoux, Pedro; Muñoz Vives, Josep Maria
Background: SARS-CoV-2 (COVID-19) has resulted in a widespread loss of lives, morbidity, and major disruptions to the healthcare system. Hip fractures are an emergent condition which require early intervention to reduce increased risk of mortality and morbidity. Infection of SARS-CoV-2 may contribute to increased mortality due to the role of infection and immune response. This study investigated the impact of COVID-19 infection (defined by clinical symptoms) on mortality following proximal femoral fracture (PFF) repair procedures. Methods: This study was a retrospective cohort study. Data from the Premier Healthcare Database ® was extracted for patients presenting for PFF during 2019 for control, and February 2020-September 2020 to represent a COVID time-period. Results: A total of N = 73 953 subjects were enrolled for the 2019 period, and a total of N = 34 842 subjects were enrolled for the COVID period. For the 2019 period, subjects who had a PFF procedure and who had flu/COVID-like illness had 2.47 (CI:2.11, 2.88) times the odds of mortality compared to those who did not have flu/COVID-like illness. Subjects who had a PFF procedure and who had flu/COVID-like illness during the COVID period had 2.85 times (CI:2.36, 3.42) the odds of mortality compared to those who did not have flu/COVID-like illness. For the COVID period, within subjects who did not have a PFF procedure, those with flu/COVID-like illness had increased odds of mortality compared to those who did not have flu/COVID-like illness (OR:2.26, CI:1.57, 3.21). Conclusions: Hip fractures present high risk for mortality and morbidity, where timely intervention is critical to improved outcomes. Presence of infection such as flu/COVID-like illness may influence mortality in patients undergoing hip fracture repair procedures. Consideration of infection status as a comorbidity is important to proper management and achieving optimal outcomes.